2013
DOI: 10.1113/jphysiol.2012.242750
|View full text |Cite
|
Sign up to set email alerts
|

Failure of action potential propagation in sensory neurons: mechanisms and loss of afferent filtering in C‐type units after painful nerve injury

Abstract: Key points• The peripheral terminals of sensory neurons encode physical and chemical signals into trains of action potentials (APs) and transmit these trains to the CNS.• Although modulation of this process is thought to predominantly reside at synapses, there are also indications that AP trains are incompletely propagated past points at which axons branch. One such site is the T-junction, where the single sensory neuron axon branches into peripheral and central processes.• In recordings from sensory neurons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(140 citation statements)
references
References 92 publications
(190 reference statements)
9
127
1
3
Order By: Relevance
“…All testing was completed within three minutes following GFS. On the basis of prior studies and our own collision experiments using this preparation , recording of either a full AP or a reduced electrotonic residue in the soma was considered evidence of successful passage of an AP through the DRG, whereas complete failure of somatic depolarization was interpreted as failure of AP propagation through the DRG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All testing was completed within three minutes following GFS. On the basis of prior studies and our own collision experiments using this preparation , recording of either a full AP or a reduced electrotonic residue in the soma was considered evidence of successful passage of an AP through the DRG, whereas complete failure of somatic depolarization was interpreted as failure of AP propagation through the DRG.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we determined the ability of the recorded neuron to conduct APs through the DRG, which we quantified by identifying the maximal rate of APs in trains that successfully transited the DRG without AP failure. This last measure is relevant because the T‐junction where the stem axon of the pseudounipolar sensory neuron branches into the peripheral process and central process is a point of low safety factor for AP propagation due to impedance mismatch at that site, by which process the T‐junction functions as a low‐pass filter for afferent sensory traffic .…”
Section: Introductionmentioning
confidence: 99%
“…Electrical stimulation of nerve fibers with 100-Hz bursts is a common stimulation protocol to induce synaptic LTP (Ruscheweyh et al 2011). It has been shown that not all C fibers can follow this high frequency (Fang et al 2005;Gemes et al 2013;Lawson 2002;Raymond et al 1990). However, so far it remains unknown if slowly-conducting muscle and skin afferents differ systematically in their ability to follow electrical HFS.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…We have identified dysfunction of these processes in axotomized neurons following painful nerve injury, including elevated function of the plasma membrane Ca 2+ -ATPase (PMCA) (Gemes et al, 2012b), accompanied by decreased resting cytoplasmic Ca 2+ ([Ca 2+ ] c ) (Fuchs et al, 2005), reduced function of the sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase (SERCA) (Duncan et al, 2013) that reduces ER Ca 2+ stores (Gemes et al, 2009; Rigaud et al, 2009), with resulting elevation of store-operated Ca 2+ entry (SOCE) (Gemes et al, 2011) and diminished release of Ca 2+ from stores upon neuronal activity through the process of Ca 2+ -induced Ca 2+ release. Together, these disturbances of Ca 2+ signaling contribute to elevated generation and transmission of high-frequency trains of action potentials in the injured sensory neurons (Gemes et al, 2009; Gemes et al, 2012a; Hogan et al, 2008; Lirk et al, 2008; Sapunar et al, 2005; Tang et al, 2012). …”
Section: Introductionmentioning
confidence: 99%